Minnowbrook: the search for a new reality - Gawthrop, Louis C. (1997)
The search for a public administration reality begins with issues of theory as a substitute for reality. These illusions of theoretical construct have not corrupted public administration, in part because of Minnowbrook I. In a time of national crisis the papers of Minnowbrook I set out an ethic and perspective seriously informed by the reality of the 1968 National Advisory Commission on Civil Disorders (the Kerner Commission) and in 1988, Minnowbrook II is informed by the Commission on the Cities (a twenty year update of the Kerner Commission Report). The Minnowbrook I papers are an example of the whole being more important than the sum of its parts. Both conferences as well as the papers they produced are grounded in reality, in a shared commitment to making democratic self-government work, and in achieving sensible notions of effectiveness, equity, human dignity, and trust free from the corrupting effects of theory. - Reproduced
Keywords: Public administration